Characterization of buffalo milk production system in Bangladesh (Bangladesh Journal of Animal Science, 2016)
This survey study was conducted in Tangail, Jamalpur, Bogra, Sirajganj, Pabna and Thakurgaon districts for household farming, and in Bhola, Noakhali, Lakshmipur and Patuakhali districts for bathan farming to undertake an assessment on the management factors in household and bathan farming for identifying the potentiality and constraints in milk production from buffalo. A 90 number of pre-designed questionnaire was used for data collection by direct interviewing of buffalo farmers. From this study, it was revealed that 82% of the farmers have 1 to 3 buffalo per household and 73% of the farmers have 51 to 200 buffalo per bathan. Buffaloes were raised in homestead and approximately 5-7 hours were grazes per day in household farming. Small quantity of concentrate feeds were offered to buffalo by the rich farmers during dry season. On the other hand, in bathan, farmers were fully depended to feed the buffalo on grazing at public land. In household, the average daily milk production was 3 to 8 liters and total milk yield was 799 liters in a lactation length of 270 days. In bathan, the average daily milk production was 1 to 2 liters and total milk yield was 435 liters in a lactation length of 215 days. The average age of first calving, service per conception, gestation period and calving interval were 39 months, 1.9 numbers, 310 days and 490 days, respectively in household farming. The average age of first calving, service per conception, gestation period and calving interval were 40 months, 2.1 numbers, 315 days and 530 days, respectively in bathan farming; however, further study is required on the buffalo nutrition in the bathan farming.Bang. J. Anim. Sci. 2016. 45 (1):69-77